Firm size and solvency performance of wood-based companies listed in Bursa Malaysia - Chang, Wai Loong (2019)
Previous studies on the relationship between the firm size and solvency performance has been insufficient especially in wood-based industry. Thus, this study was conducted to determine the relationship of firm size and solvency performance as well as to investigate the impact of firm size’s indicators toward the solvency performance of wood-based listed companies in Bursa Malaysia. The Pearson correlation results showed that both indicators of firm size, total assets and share capital, had a positive significant relationship with the indicators of solvency performance, which are debt-to-asset ratio and debt-to-equity ratio. The multiple linear regression results for the two models showed that only total assets caused an impact to the indicators of solvency performance. Results of this study are useful to several relevant parties such as managers, creditors and shareholders. Future study should investigate on other variables especially on the determinants of solvency performance.